Stoichiometry on the edge—humans induce strong imbalances of reactive C:N:P ratios in streams. (1st April 2023) - Wachholz, Alexander; Dehaspe, Joni; Ebeling, Pia; Kumar, Rohini; Musolff, Andreas; Saavedra, Felipe; Winter, Carolin; Yang, Soohyun; Graeber, Daniel
Abstract: Anthropogenic nutrient inputs led to severe degradation of surface water resources, affecting aquatic ecosystem health and functioning. Ecosystem functions such as nutrient cycling and ecosystem metabolism are not only affected by the over-abundance of a single macronutrient but also by the stoichiometry of the reactive molecular forms of dissolved organic carbon (rOC), nitrogen (rN), and phosphorus (rP). So far, studies mainly considered only single macronutrients or used stoichiometric ratios such as N:P or C:N independent from each other. We argue that a mutual assessment of reactive nutrient ratios rOC:rN:rP relative to organismic demands enables us to refine the definition of nutrient depletion versus excess and to understand their linkages to catchment-internal biogeochemical and hydrological processes. Here we show that the majority (94%) of the studied 574 German catchments show a depletion or co-depletion in rOC and rP, illustrating the ubiquity of excess N in anthropogenically influenced landscapes. We found an emerging spatial pattern of depletion classes linked to the interplay of agricultural sources and subsurface denitrification for rN and topographic controls of rOC. We classified catchments into stoichio-static and stochio-dynamic catchments based on their degree of intra-annual variability of rOC:rN:rP ratios. Stoichio-static catchments (36% of all catchments) tend to have higher rN median concentrations, lower temporal rN variability and generally low rOC medians. Our results demonstrate the severe extent of imbalances in rOC:rN:rP ratios in German rivers due to human activities. This likely affects the inland-water nutrient retention efficiency, their level of eutrophication, and their role in the global carbon cycle. Thus, it calls for a more holistic catchment and aquatic ecosystem management integrating rOC:rN:rP stoichiometry as a fundamental principle.